Konsep desain lanskap Stasiun Kedungjati Kabupaten Grobogan Jawa Tengah - Andriyani, Novia; Kohdrata, Naniek; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020DO - 10.24843/JAL.2020.v06.i02.p05, 2020)
Landscape Design Concept of Kedungjati Train Station in Grobogan Regency Central Java. Kedungjati train station is one of the oldest stations in Indonesia which was built by NISM (Nederlandsh Indische Spoorweg Maatschappij). It was inaugurated in 21 May 1873. Kedungjati Station is currently expanding its functions. There are some activities that do not support or threatening future concervation goals of the train station, since there a no landscape design concept yet. Therefore, it is necessary to have a conceptual design planning as a start of supporting the Kedungjati train station site conservation an development.This study aims to determine the additional of functions at the Kedungjati Station and share zones of the Kedungjati Station so that it can support preservation of station historic buildings by accommodating current functions. The concept of landscape design at Kedungjati Station is done by collecting biophysical, social, historical and managerial policies on the site, then analyzing and synthesizing. Some old features of the train facilities shall be conserved and utilize as object of interest at the station.The concept of landscape design that supports the preservation of buildings as cultural heritage buildings is the Indis landscape design concept.